(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The role of the NHRC in protecting the human rights of the victims is very proactive in spite of various challenges before the commission. This study highlights the problems and challenges of the commission to overcome the same. Although the contemporary scenario is the time of human rights and constitutional rights.